Diagnostic Accuracy of Electrical Impedance Spectroscopy in Non-melanoma Skin Cancer - Esra Sarac; Andreas Meiwes; Thomas Eigentler; Stephan Forchhammer; Lukas Kofler; Hans-Martin Häfner; Claus Garbe (Medical Journals Sweden, 2020)
Electrical impedance spectroscopy is a non-invasive technique that can help clinicians in diagnosing malignant skin tumours. Depending on the cellular irregularity of the lesion, electrical impedance spectroscopy can reveal changes in the structure and form of the cells, using a harmless electrical current applied to the skin. A score between 0 and 10 is generated by the electrical impedance spectrometer, where 0 is considered benign and 10 is malignant. This prospective study was conducted in 101 patients with a total of 200 skin lesions; 62 benign and 138 malignant. There was a significant difference between the electrical impedance of malignant and benign lesions (p < 0.001). The sensitivity, specificity, positive predictive value and negative predictive value of electrical impedance spectroscopy for non-melanoma skin cancer were 94.2%, 41.9%, 78.3% and 76.5%, respectively, when the cut-off for the electrical impedance spectroscopy score was set at between 5 and 6. The area under the curve in receiver operating characteristics analyses was 0.758.